Sleep, inflammation, and hemodynamics in rodent models of traumatic brain injury - Green, Tabitha R. F.; Carey, Sean D.; Mannino, Grant; Craig, John A.; Rowe, Rachel K.; Zielinski, Mark R. (Frontiers in Neuroscience, 2024)
Traumatic brain injury (TBI) can induce dysregulation of sleep. Sleep disturbances include hypersomnia and hyposomnia, sleep fragmentation, difficulty falling asleep, and altered electroencephalograms. TBI results in inflammation and altered hemodynamics, such as changes in blood brain barrier permeability and cerebral blood flow. Both inflammation and altered hemodynamics, which are known sleep regulators, contribute to sleep impairments post-TBI. TBIs are heterogenous in cause and biomechanics, which leads to different molecular and symptomatic outcomes. Animal models of TBI have been developed to model the heterogeneity of TBIs observed in the clinic. This review discusses the intricate relationship between sleep, inflammation, and hemodynamics in pre-clinical rodent models of TBI.